Analysis of influence on driver behaviour while using in-vehicle traffic lights with application of head-up display - Yang, Bo; Zheng, Rencheng; Yin, Yuandong; Yamabe, Shigeyuki; Nakano, Kimihiko (IET intelligent transport systems, 2016)
Emerging vehicular communication makes it possible to provide traffic light information to drivers inside vehicles with the application of in-vehicle devices. However, the effect of this method on driver behaviour is still unclear, and there is concern that the application of in-vehicle traffic lights may result in driver distraction. This study proposed two modes of in-vehicle traffic lights to assist drivers: a ‘current’ mode providing real-time information of the upcoming ground traffic lights, and a ‘predicted’ mode offering predicted information regarding ground traffic lights, taking into account the time to arrival at the upcoming intersection. Two kinds of in-vehicle devices were compared for displaying in-vehicle traffic lights: a normal 4.3-inch display and a head-up display. A driving simulator experiment was executed for 11 subjects, and driver behaviour was evaluated for driving operations and eye-gaze behaviour. The results demonstrated that disruptive braking and accelerating operations were significantly reduced under the predicted mode, and glance time was significantly shorter for the head-up display than for the normal 4.3-inch display. The authors concluded that the predicted mode easily prompts drivers to ecological driving, and that the head-up display is reliable for providing in-vehicle traffic light information.